Plumbagin induces autophagy and apoptosis of SMMC‐7721 cells in vitro and in vivo. Issue 6 (9th December 2018) - Lin, Yuning; Chen, Yongxin; Wang, Shengshan; Ma, Jing; Peng, Yue; Yuan, Xianling; Lv, Beibei; Chen, Wanjun; Wei, Yanfei
Abstract: Plumbagin (PL), an active naphthoquinone compound, has been demonstrated to be a potential anticancer agent. However, the underlying anticancer mechanism is not fully understood. In this study, the human hepatocellular carcinoma (HCC) SMMC‐7721 cell line was studied in an in vitro model. The cell proliferation was inhibited by PL in a dose‐ and time‐dependent manner. Electron microscopy, acridine orange staining, and immunofluorescence were used to evaluate autophagosome formation and LC3 protein expression in PL‐treated SMMC‐7721 cells. Real‐time polymerase chain reaction and Western blot showed that PL treatment suppressed the expression of apoptosis and autophagy factors (LC3, Beclin1, Atg7, and Atg5), which are associated with tumor apoptosis and autophagy in SMMC‐7721 cells. In the study of in vitro tumor nude mouse models, PL can inhibit tumor growth. Cell apoptosis and autophagy of the transplanted tumors were evaluated by hematoxylin and eosin staining, terminal deoxynucleotidyl transferase‐mediated dUTP nick end‐labeling staining, and Western blot. In addition, in the in vivo studies of HCC cells, we found that pretreatment with the autophagy inhibitor 3‐methyladenine blocked the formation of apoptosis induced by PL. In contrast, administration of the apoptosis inhibitor Z‐VAD did not affect PL‐induced autophagy. Taken together, our findings strongly suggest that PL is a promising drug with significant antitumor activity in HCC. Abstract : Plumbagin (PL) can upregulate the expression levels of autophagy genes and proteins in hepatocellular carcinoma (HCC) cells and promote apoptosis and autophagic death. In addition, the inhibition of apoptosis can enhance PL promotion of autophagy, but the specific mechanism of PL‐induced hepatoma cell apoptosis and autophagy regulation remains to be further studied. This study provides a theoretical and experimental basis for the development of clinical application of PL in the treatment of HCC.